Caste and Construction of a Tharu Subjectivity in Resham Chaudhary's Selected Novels - Dangaura, Mohan (Literary Studies, 2023)
This paper studies the role of caste, community, and culture in the formation of Tharu subjectivity in Resham Chaudhary's novels Chirphar (Breakdown), Bandhuwa Kamaiya, and Hidden Stories from Prison. Tharu subjectivity in Chaudhary's novels has been represented as the culturally distinguished, however, socio-politically oppressed body. Chaudhary's narratives mention his experiences of the time when Kamaiya system was in practice. Chaudhary discusses Kamaiya Tharus as the most acute representation of social status of Tharu community. The text primarily makes commentary on the shaping of Tharu subjectivity in his community. The author critically delves into the historical growth of the community, dividing it into Landlord Tharu and Kamaiya Tharu. Furthermore, the author becomes critical of his own community in terms of upbringing and social interaction. He expresses his dissatisfaction with the community's politically depraved conscience. He makes harsh and pitiful comments on the Tharu community's uncaring and self-observed behavior among themselves. The author begins his text by remembering his life-changing experience in America, where he was first advised to return to his own village home and start a movement for promoting the ethnic agency of his community. Chaudhary's autobiographical novels also assort memories of different periods of his exiled life in India. Hence, the paper assesses that the author has been the victim of his own community's naive and unwitting socio-political structure and the depraved Tharu subjectivity is formed by the depraved socio-political conscience of its community